IL‐31 levels correlate with pruritus in patients with cholestatic and metabolic liver diseases and is farnesoid X receptor responsive in NASH. Issue 1 (17th January 2023) - Xu, Jun; Wang, Ya; Khoshdeli, Mina; Peach, Matt; Chuang, Jen‐Chieh; Lin, Julie; Tsai, Wen‐Wei; Mahadevan, Sangeetha; Minto, Wesley; Diehl, Lauri; Gupta, Ruchi; Trauner, Michael; et al.
Abstract : Background and Aims: Pruritus is associated with multiple liver diseases, particularly those with cholestasis, but the mechanism remains incompletely understood. Our aim was to evaluate serum IL‐31 as a putative biomarker of pruritus in clinical trials of an farnesoid X receptor (FXR) agonist, cilofexor, in patients with NASH, primary sclerosing cholangitis (PSC), and primary biliary cholangitis (PBC). Approach and Results: Serum IL‐31 was measured in clinical studies of cilofexor in NASH, PSC, and PBC. In patients with PSC or PBC, baseline IL‐31 was elevated compared to patients with NASH and healthy volunteers (HVs). IL‐31 correlated with serum bile acids among patients with NASH, PBC, and PSC. Baseline IL‐31 levels in PSC and PBC were positively correlated with Visual Analog Scale for pruritus and 5‐D itch scores. In patients with NASH, cilofexor dose‐dependently increased IL‐31 from Week (W)1 to W24. In patients with NASH receiving cilofexor 100 mg, IL‐31 was higher in those with Grade 2–3 pruritus adverse events (AEs) than those with Grade 0–1 pruritus AEs. IL‐31 weakly correlated with C4 at baseline in patients with NASH, and among those receiving cilofexor 100 mg, changes in IL‐31 and C4 from baseline to W24 were negatively correlated. IL‐31 messenger RNA (mRNA) was elevated in hepatocytes from patients with PSC and NASH compared to HVs. In a humanized liver murine model, obeticholic acid increased IL‐31 mRNA expression in human hepatocytes and serum levels of human IL‐31. Conclusions: IL‐31 levels correlate with pruritus in patients with cholestatic disease and NASH, with FXR agonist therapy resulting in higher serum levels in the latter group. IL‐31 appears to derive in part from increased hepatocyte expression. These findings have therapeutic implications for patients with liver disease and pruritus. Abstract :